Prevalence of obesity among adolescents: a facility-based study - Manoli, Aniketh D.; Kambar, Sanjay S.; Wali, Abhinandan R. (International Journal Of Community Medicine And Public Health, 2022)
Background: Obesity and overweight are described as abnormal or excessive fat accumulation that poses a health risk. Obesity has become a global health issue, with obesity being generally recognized as a major risk factor for coronary heart disease, hypertension, diabetes, and a variety of other illnesses. Childhood obesity is one of the major health challenges in every country across the world. The goal of this study was to determine the prevalence of obesity among teenagers and its relationship to sociodemographic parameters. Methods: The estimated sample size is n=204 we included n=215 cases coming to OPD at primary health center Vantamuri. Following the completion of the questionnaire, height and weight parameters were measured and recorded. Weight (kg) was measured using a weighing scale with a 0.1 kg error margin without shoes or heavy clothes; the weighing scale was calibrated regularly using established reference weights. Results: Out of the total n=215 cases included in the study n=98 (45.5%) were males and n=117 (54.4%) were females. In most of the cases in the study n=151 (70.2%) were performing physical activity only sometimes and n=26 (12%) did not perform any physical activity. Only 17.6% of cases performed some form of physical activity frequently. In this study, we found that 34.8% of cases were in the overweight category and 26.9% in the obese category. The incidence of fast-food consumption was every day and frequently found in 29% and 33% respectively. Conclusions: Obesity and overweight are preventable by establishing school-based awareness programs and educating parents about healthy lifestyle management, so indirectly avoiding chronic illness in adulthood. Children should be encouraged to participate more frequently in physical activities.